Abnormal Temperature Dependence of the Coercive Feld in FePt thin ﬁlms - Guzmán, Jonás Manuel (2013)
We have observed notable changes in the magnetic response of FePt thin films that we have attributed to a transition in the magnetic domain structure when the film thickness or the temperature is varied. The critical thickness for this transition depends on the Q-factor, Q=Kperp/2PiMs^2, so that a change in thedomain structure is expected when changes in the perpendicular anisotropy, Kperp , or the saturation magnetization, Ms, occur. At room temperature these samples have Q ~ 0:3, and a transition between planar to stripe-like domains occurs for a film thickness d ~ 30 nm. Due to the different thermal expansion of the FePt alloy and the Si substrate a reduction in Q is predicted when the temperature is lowered. From magnetization vs. field loops measured at different temperatures below T=300 K, we have effectively observed a change in the coercive field which can be associated to a transition from stripe-like to in-plane domains. The transition temperature range is broad, indicating a gradual variation between the two magnetic configurations, but changes systematically with film thickness, consistent with an interfacial induced stress. A model that includes the temperature dependence of the strain and the magnetization, predicts correctly the observation of a larger critical thickness at lower temperatures.